Pengaruh Pembiayaan Bermasalah Terhadap Profitabilitas Bank Muamalat KCP Kisaran dengan Dana Pihak Ketiga sebagai Variabel Moderating - Junita Sari; Nurul Jannah (Universitas Muhammadiyah Enrekang, 2022)
This research aims to find out how much Problematic Financing have on Profitability with Third Party Funds as moderating variables at mualamat KCP Kisaran Bank. This type of research with a statistical descriptive approach. The research methodology used is a method of documentation and study of literature. The data source comes from secondary data, which comes from mualamat KCP Kisaran Bank. The data used in this study is data on mualamat KCP Kisaran Bank on January 2018 to December 2022. The analytical tools used in this study are multiple linear regressions. The results of this study show that Problematic Financing negatively and significantly affects profitability, while Third Party Funds also do not moderate the effect of Problematic Financing on profitability